Assessment tools of immediate risk of self-harm and suicide in children and young people: A scoping review. (June 2019) - Carter, Tim; Walker, Gemma M; Aubeeluck, Aimee; Manning, Joseph C
There are increasing numbers of children presenting to paediatric hospital settings in mental health crisis. Typically, non-mental health professionals are responsible for the initial assessment of these children and are required to identify immediate physical and emotional health needs. To ensure the safety of these children, immediate risk of suicide and self-harm should be assessed. However, no standardized assessment tool is used in clinical practice, and for those tools that are used, their validity and reliability is unclear. A scoping review was conducted to identify the existing assessment tools of immediate self-harm and suicide risk. Searches of electronic databases and relevant reference lists were undertaken. Twenty-two tools were identified and most assessed acute risk of suicide with only four tools incorporating a self-harm assessment. The tools varied in number of items (4–146), subscales (0–11) and total scores (16–192). Half incorporated Likert-type scales, and most were completed via self-report. Many tools were subject to limited psychometric testing, and no single tool was valid or reliable for use with children presenting in mental health crisis to non-mental health settings. As such, a clinically appropriate, valid and reliable tool that assesses immediate risk of self-harm and suicide in paediatric settings should be developed.